Clinical and Histopathological Features of Breast Cancer in Iraqi Patients between 2018-2021 - Mohsin, Raghdah Naser; Mohamad, Ban Jasim (Iraqi Journal of Science, 2024)
Breast cancer (BC) is the most common malignancy in women worldwide and a major cause of cancer-related deaths for women in Iraq. This assignment was created to investigate the characteristics of BC diagnosed in Baghdad from 2018 to 2021. A total of eighty-nine of paraffin embedded tissue blocks of different breast tissue tumors (71 females and 18 males) with their data, were collected from archive of Histopathology Department, Teaching Laboratories of Medical City, Al-Yarmouk Teaching Hospital, and a private laboratory in Baghdad-Iraq. The clinical information regarding age, gender, tumor size, tumor stage and grade, lymph nodes metastasis, in addition to the findings of estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor (HER)-2 and molecular subtypes were obtained from reviewed patients medical records and pathologic reports. Results revealed a high incidence of BC in patients at sixth and seventh decades of age, with a rate of 37.78% and 28.89% respectively. The dominant tumor size was 2–5 cm in malignant cases, and 91.11% of cases were in females. Regarding the histological type, the majority of malignant cases (60%) were IDCs. Whereas 53.33% of cases had metastasis to lymph nodes. Stage III was the most common tumor stage and grade II was the most common grade, comprising 64.44%. Furthermore, the hormone receptor status was 46.67% ER positive, while PR results were equally positive and negative comprising 42.22% per each, 62.22% of HER2 status was negative, and luminal subtypes accounted for 46.67% of all molecular subtypes.